A Cr2CO2 monolayer as a promising cathode for lithium and non-lithium ion batteries: a computational exploration. Issue 85 (30th August 2016) - Li, Fengyu; Cabrera, Carlos R.; Wang, Jingyang; Chen, Zhongfang
Abstract : By means of density functional theory (DFT) computations, we investigated the potential of oxygen-terminated Cr2 C (Cr2 CO2 ) as a cathode material for lithium and non-lithium ion batteries (LIBs and NLIBs). Abstract : By means of density functional theory (DFT) computations, we investigated the potential of oxygen-terminated Cr2 C (Cr2 CO2 ) as a cathode material for lithium and non-lithium ion batteries (LIBs and NLIBs). Our computations revealed that the Cr2 CO2 exhibits the extraordinary characteristics that the LIB and NLIB electrodes require, including good electronic conductivity, high binding energy, a moderate diffusion barrier and high storage capacity. In particular, the high operating voltage (>2 V) of Cr2 CO2 endows itself as a promising cathode material for Li, Na and Ca ion batteries.